Impact of gender on 10-year outcome after coronary artery bypass grafting. (17th May 2021) - Barili, Fabio; D'Errigo, Paola; Rosato, Stefano; Biancari, Fausto; Forti, Marco; Pagano, Eva; Parolari, Alessandro; Gellini, Mara; Badoni, Gabriella; Seccareccia, Fulvia
Abstract: OBJECTIVES: Our goal was to evaluate the impact of gender on the 10-year outcome of patients after isolated coronary artery bypass grafting (CABG) included in the Italian nationwide PRedictIng long-term Outcomes afteR Isolated coronary arTery bypass surgery (PRIORITY) study. METHODS: The PRIORITY project was designed to evaluate the long-term outcomes of patients who underwent CABG and were included in 2 prospective multicentre cohort studies. The primary end point of this analysis was major adverse cardiac and cerebrovascular events. Baseline differences between the study groups were balanced with propensity score matching and inverse probability of treatment. Time to events was analysed using Cox regression and competing risk analysis. RESULTS: The study population comprised 10 989 patients who underwent isolated CABG (women 19.6%). Propensity score matching produced 1898 well-balanced pairs. The hazard of major adverse cardiac and cerebrovascular event was higher in women compared to men [adjusted hazard ratio (HR) 1.13, 95% confidence interval (CI) 1.03–1.23; P = 0.009]. The incidence of major adverse cardiac and cerebrovascular event in women was significantly higher at 1 year (HR 1.31, 95% CI 1.11–1.55; P < 0.001) and after 1 year (HR 1.11, 95% CI 1.00–1.24; P = 0.05). Mortality at 10 years in the matched groups was comparable (HR 1.04, 95% CI 0.93–1.16; P = 0.531). Women have significantly a higher 10-year risk of myocardial infarction (adjusted HR 1.40, 95% CI 1.17–1.68; P = 0.002) and percutaneous coronary intervention (adjusted HR 1.32, 95% CI 1.10–1.59; P = 0.003). CONCLUSIONS: The present study documented an excess of non-fatal cardiac events after CABG among women despite comparable 10-year survival with men. These findings suggest that studies investigating measures of tertiary prevention are needed to decrease the risk of adverse cardiovascular events among women. Abstract : Over the last 2 decades clinicians and policy makers have recognized the need for gender-specific medicine [1].